Annona Muricata L Leaf Infusion Effect on Glucose Absorption in the Intestinal Cells Membrane of Wistar Rats Model - Vycke Yunivita; Putra Haqiqie Adnantama Lubis; Augusta Y. L. Arifin (Althea Medical Journal, 2019)
Background: Diabetes mellitus (DM) is a chronic disease that disrupts the homeostasis of glucose. DM is the second of most causes of deaths in urban areas, as well as the sixth in rural areas. Therefore, herbal medicine is constantly developed. Soursop leaves have been long known to have good effects in lowering glucose levels in our blood. This study explored the soursop leaves infusion on glucose absorption in the intestinal cell membrane of the Wistar Rats Model. Methods: This was an exploratory study performed in October 2012 on five male rats Wistar, aged 3-4 months, weighing about 150-300 grams. Using the in situ perfusion method, each rat was given the following; 3 X 10-3 M glucose solution for one hour; 3 X 10-3 M glucose solution with 1 mL of infusion of soursop leaves (Annona muricata L) for one hour; 3 X 10-3 M glucose solution for the last hour. The glucose absorption levels were measured using spectrophotometry method. The glucose level between treatments was analyzed using a paired sample t-test.Results: The concentration of glucose absorption was decreased, the first treatment was 24.42+14.29 mg/dL, the second treatment was 18.63+10.37 mg/dL, and the third treatment was 18.24+8.02mg/dL), however, the decrease of glucose absorption was statistically not significant.Conclusions: There is a slightly decreased of the glucose absorption in the intestinal cell membranes of the Wistar Rats Model after infusion of soursop leaves. Further study is needed to explore the role of soursop leaves infusion in glucose absorption.